2015
DOI: 10.1108/cg-07-2013-0097
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting and assurance in Portugal

Abstract: Purpose – The purpose of this paper is to provide a descriptive comprehensive analysis of sustainability reporting (SR) and assurance in Portugal after the onset of the most recent economic crisis. Design/methodology/approach – The authors analyze 290 sustainability reports for the years 2008, 2009, 2010 and 2011, and find those that include assurance statements and characterize them. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…Perego and Kolk (2012) analysed assurance practices among the G250 firms, and pointed out that most of assurance providers used the ISAE 3000 in combination with other standards. Ferreira Gomes et al (2015) studied assurance among Portuguese companies and revealed that the dominant standard used was the ISAE 3000. Gürtürk and Hahn (2016) analysed the assurance statements in the sustainability reports issued by UK FTSE 100 companies, and German DAX and MDAX companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perego and Kolk (2012) analysed assurance practices among the G250 firms, and pointed out that most of assurance providers used the ISAE 3000 in combination with other standards. Ferreira Gomes et al (2015) studied assurance among Portuguese companies and revealed that the dominant standard used was the ISAE 3000. Gürtürk and Hahn (2016) analysed the assurance statements in the sustainability reports issued by UK FTSE 100 companies, and German DAX and MDAX companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scope of assurance in all the cases has been varying between the entire report and some specified sections. This shows a lack of consistency in doing so and therefore the level of assurance has also been fluctuating from reasonable/high and limited/moderate (Branco, Delgado, Ferreira Gomes, & Cristina Pereira Eugénio, ; Gomes, Eugénio, & Branco, ; Marx & van Dyk, ; Sawani, Mohamed Zain, & Darus, ). In all the cases, companies have complied with Assurance Standard ISAE 3000 from the beginning of their reporting journey but have only recently shifted to Assurance Standard AA 1000 AS.…”
Section: Evolutionary Patterns and Profiling Of The Selected Casesmentioning
confidence: 99%
“…Of all the standards that are available, the GRI guidelines are the most influential guidelines adopted by various organisations in preparing SR (Gomes et al, 2015), aiming to establish a generally accepted framework (Bebbington et al, 2014). The GRI guidelines target on the TBL by analysing information that is applicable and material to organisations for stakeholder's interest (GRI, 2013).…”
Section: Gri Guidelinesmentioning
confidence: 99%
“…The GRI guidelines target on the TBL by analysing information that is applicable and material to organisations for stakeholder's interest (GRI, 2013). The analysis finds that 78 percent of the best 100 organizations within 41 nations and 82 percent of the highest ranking within 250 organizations from the Global Fortune 500 use these guidelines (Gomes et al, 2015). GRI was established in 1997 and have been formally published since 2000 by the Coalition for Environmentally Responsible Economies (CERES) and the United Nations Environmental Programme (UNEP) (Isaksson and Steimle, 2009).…”
Section: Gri Guidelinesmentioning
confidence: 99%